Developmental origins and homologies of the hyracoid dentition. Issue 4 (30th April 2020) - Gomes Rodrigues, Helder; Tabuce, Rodolphe; Asher, Robert J.; Hautier, Lionel
Abstract: Understanding the origins of morphological specializations in mammals is a key goal in evolutionary biology. It can be accomplished by studying dental homology, which is at the core of most evolutionary and developmental studies. Here, we focused on the evolution and development of the specialized dentition of hyraxes for which dental homologies have long been debated, and could have implications on early placental evolution. Specifically, we analysed dental mineralization sequences of the three living genera of hyraxes and 17 fossil species using X‐ray computed microtomography. Our results point out the labile position of vestigial upper teeth on jaw bones in extant species, associated with the frequently unusual premolar shape of deciduous canines over 50 Ma of hyracoid evolution. We proposed two evolutionary and developmental hypotheses to explain these original hyracoid dental characteristics. (a) The presence of a vestigial teeth on the maxilla in front of a complex deciduous canine could be interpreted as extra‐teeth reminiscent of early placental evolution or sirenians, an order phylogenetically close to hyracoids and showing five premolars. (b) These vestigial teeth could also correspond to third incisors with a position unusually shifted on the maxilla, which could be explained by the dual developmental origin of these most posterior incisors and their degenerated condition. This integrative study allows discussion on the current evolutionary and developmental paradigms associated with the mammalian dentition. It also highlights the importance of nonmodel species to understand dental homologies. Abstract : Illustration of vestigial teeth in an embryo of extant hyrax ( Heterohyrax )